Transformational–Spiritual Leadership in HRM and Lecturer Competence at Indonesian Islamic Universities - Ali Abdul Wakhid; Idrus Ruslan; Arifeen Yama (Jurnal Ilmiah Peuradeun, 2026)
Human resource management (HRM) at State Islamic Higher Education Institutions (PTKIN) has predominantly emphasized administrative efficiency and academic performance, while the integration of transformational leadership and spiritual values remains insufficiently institutionalized. This study aims to analyze how integrating transformational–spiritual leadership into HRM practices strengthens lecturer competence in PTKIN in Indonesia. Employing a qualitative descriptive-analytical approach with a multi-site design, the study was conducted at UIN Raden Intan Lampung, UIN Sunan Gunung Djati Bandung, and IAIN Ponorogo. Data were collected through in-depth interviews, observations, and document analysis involving institutional leaders, senior and junior lecturers, and purposively selected students. The findings reveal that transformational–spiritual leadership is systematically operationalized within HRM practices, particularly in lecturer recruitment, professional development, performance evaluation, and participatory decision-making processes. This integration shapes lecturer competence not only in academic and professional dimensions but also in personal integrity, intrinsic motivation, ethical commitment, and service orientation. The study contributes to leadership and higher education governance literature by demonstrating that transformational–spiritual leadership functions as an integrated governance logic rather than a symbolic or individual leadership attribute. Practically, the findings offer a strategic framework for PTKIN to enhance academic competitiveness while preserving Islamic identity and moral legitimacy within the global higher education landscape.